Does a relationship exist between the development of the banking sector and the economic growth of Eurozone? - Černohorská, Liběna; Kula, Vojtěch (Varazdin Development and Entrepreneurship Agency, 2016)
The goal of this paper is to discover the relationship between select banking sector indicators and the economic growth of the Eurozone. Loans provided by banks to the private non-financial sector and the M3 banking aggregate were chosen from among select banking sector indicators. The Eurozone’s economic growth was evaluated using the development of GDP. The aforementioned relationship between these values is analyzed using the Engle-Granger cointegration test. These tests are conducted on select statistical data from the years 2000 to 2013. In order to be able to proceed to testing the cointegration of the time series using the Engle-Granger test, it was necessary to eliminate the series that do not meet the basic prerequisites – consequently, the existence of a unit root, i.e. the non-stationarity of the original time series. In light of the results of the Dickey-Fulller test, it was necessary to eliminate the time series of year-to year changes in GDP. On the basis of these tests, it was found that there is no cointegration relationship between any time series at a level of significance of 0.05; this means that no long-term relationship was found between the amount of bank loans provided to the private non-financial sector and GDP or between M3 and GDP. It is necessary to realize that the impact of the global financial crisis was being experienced during the period analyzed, i.e., between 2000 and 2013. It is possible that this is the reason why is not possible to statistically confirm the long-term positive influence of the banking sector on the economic growth of the Eurozone.
Existuje vztah mezi vývojem bankovního sektoru a ekonomickým růstem v Eurozóně?
Keywords: banking sector; cointegration test; economic growth; Eurozone; GDP; M3; bankovní sektor; test kointegrace; ekonomický růst; Eurozóna; HDP; M3